Active and reactive power flow management in parallel transmission lines using static series compensation (SSC) with energy storage - Mohammed Yahya Suliman (Institute of Advanced Engineering and Science, 2019)
The power flow controlled in the electric power network is one of the main factors that affected the modern power systems development. The Static Series Compensatior with storage energy, is a FACTS powerful device that can control the active power flow control of multiple transmission lines branches. In this paper, a simulation model of power control using static series compensator with parallel transmission lines is presented. The control system using adaptive neuro-fuzzy logic is proposed. The results show the ability of static series compensator with storage energy to control the flow of powers components